Love Ambition Of Esther In Jaume Collet Serra's Orphan Movie (2009): An Individual Psychological Approach - YANTI , NURAINI ATHIKA (2012)
This study investigates "How love ambition is reflected in Jaume Collet Serra's Orphan movie?" viewed from individual psychological approach. Therefore, this research is aimed at analyzing the structural elements of Orphan movie and describing love ambition of Esther in the story based on individual psychological approach. This research paper is qualitative research. The object of the study is Orphan movie directed by Jaume Collet Serra. The primary data source is Orphan movie itself and secondary data sources are the other sources related to the movie. the method of data collection is documentation research. The technique of data analysis is descriptive analysis. Based on the analysis, there are two conclusions. First, from the structural analysis it shows that each of the elements is interrelated to each other and forms unity. Second, from the individual psychological analysis, it shows that love can raise an ambition in human because love and hate are almost similar. So, she must get her love in right way.